Equivalent Electrical Model of an Inductor Excited by a Triangular Current Including Saturation - Jorge Rafael Gonzalez-Teodoro; Enrique Romero-Cadaval; Rafael Asensi; Vladimir Kindl (Communications - Scientific letters of the University of Zilina, 2020)
A model for an equivalent electrical circuit designed for a ferrite (3C90) inductor usually used in power converters excited by a non-sinusoidal current appropriate for use in power electronics is proposed. This study, based on 3D finite element analysis, leads to significant precision advantages over 2D analysis for non-symmetric inductors. The frequency range of the analysis for the toroidal core was between 15 kHz and 1 GHz, with different levels of excitation in non-saturation and saturation status focusing on the power loss.